Chromatographic Analysis of Bioactive Metabolites from a Traditional Food Combination of (Semi) Arid Regions—Panchkuta: Insights for Sustainable Functional Foods Development - Tripti Joshi; P. R. Deepa; Pankaj Kumar Sharma (Biology and Life Sciences Forum)
Conventional agriculture may not meet the needs of the growing human population and sustainable development. These issues necessitate a shift towards traditional foods and underutilized desert plants, offering promising sustainable agricultural and food security alternatives. ‘Panchkuta’, a blend of five plants (Prosopis cineraria, Acacia senegal, Capparis decidua, Cordia dichotoma, and Mangifera indica), is a traditional food combination from (semi) arid regions. In this study, the bioactive metabolites were identified through analytical techniques, including TLC and GC-MS analysis. Tapping these underexplored plants can help design and develop healthy functional foods and nutraceutical products.